The significance of the best puncture side bone cement/vertebral volume ratio to prevent paravertebral vein leakage of bone cement during vertebroplasty: a retrospective study - Tao Gao; Zhi-Yu Chen; Tao Li; Xu Lin; Hai-Gang Hu; Xiang-Yu Wang; Jun Zeng; Chao Wu (BMC Musculoskeletal Disorders, 2023)
Abstract Objectives To verify the clinical significance of the best puncture-side bone cement/vertebral volume ratio (PSBCV/VV%) and bone cement leakage in paravertebral veins during vertebroplasty. Methods This was a retrospective analysis of a total of 210 patients from September 2021 to December 2022, who were divided into an observation group (110 patients) and a control group (100 patients). In the observation group, patients’ preoperative computed tomography (CT) data were imported into Mimics software, and the VV was calculated using the three-dimensional (3D) reconstruction function. Then, based on the best PSBCV/VV% of 13.68% determined in a previous study, the optimal PSBCV to be injected during vertebroplasty was calculated. In the control group, vertebroplasty was performed directly using the conventional method. The incidence of cement leakage into paravertebral veins was observed postoperatively in both groups. Results There were no statistically significant differences (P > 0.05) in the evaluated indicators between the two groups pre- or postoperatively, including the anterior vertebral margin height, mid-vertebral height, injured vertebral Cobb angle, visual analogue scale (VAS) score, and Oswestry Disability Index (ODI). Intragroup comparisons showed improvements in the anterior vertebral height, mid-vertebral height, injured vertebral Cobb angle, VAS score, and ODI after surgery compared with before surgery (P < 0.05). In the observation group, there were 3 cases of cement leakage into the paravertebral veins, for a leakage rate of 2.7%. In the control group, there were 11 cases of cement leakage into the paravertebral veins, for a leakage rate of 11%. The difference in the leakage rate between the two groups was statistically significant (P = 0.016). Conclusion In vertebroplasty, preoperative VV calculations using Mimics software, combined with calculation of the PSBCV according to the best PSBCV/VV% (13.68%), can effectively prevent leakage of bone cement into paravertebral veins and further prevent serious life-threatening complications such as pulmonary embolism.